ScottKnott: A Package for Performing the Scott-Knott Clustering Algorithm in R - Jelihovschi, Enio; Faria, José Cláudio; Allaman, Ivan Bezerra (Trends in Computational and Applied Mathematics, 2014)
Scott-Knott is an hierarchical clustering algorithm used in the ANOVA context, when the researcher is comparing treatment means, with a very important characteristic: it does not present any overlapping in its grouping results. We wrote a code, in R, that performs this algorithm starting from vectors, data.frame, aov or aov.list objects. The results are presented with letters representing groups as well as in graphical way using different colors to differentiate among the distinct groups.